2018
DOI: 10.1186/s12967-018-1523-6
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillar-associated protein 4 variation in symptomatic peripheral artery disease

Abstract: BackgroundSymptomatic peripheral artery disease (PAD) is an atherosclerotic occlusive disease affecting the lower extremities. The cause of symptomatic PAD is atherosclerosis, vascular dysfunctions, impaired angiogenesis and neointima formation. Microfibrillar-associated protein 4 (MFAP4) is an extracellular matrix protein, which is highly expressed in the heart and arteries and recently introduced as a potential mediator of pathological vascular remodeling and neointima formation. We aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…Another finding of our study was that the AR in our patient group was significantly greater than in the control group, and that this elevation was positively correlated with MFAP4. Previous experimental and clinical studies have both shown that MFAP4 is associated with vascular remodeling [10,23]. In the light of these findings, we think that MFAP4 may be associated with AR dilation in the patient group.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Another finding of our study was that the AR in our patient group was significantly greater than in the control group, and that this elevation was positively correlated with MFAP4. Previous experimental and clinical studies have both shown that MFAP4 is associated with vascular remodeling [10,23]. In the light of these findings, we think that MFAP4 may be associated with AR dilation in the patient group.…”
Section: Discussionsupporting
confidence: 53%
“…The authors interpreted this MFAP4 elevation as a potential marker of adaptive vessel wall alteration in chronic joint diseases. Hemstra et al [10] followed up 286 patients with peripheral artery disease for 7 years and suggested that serum MFAP4 levels were related to cardiovascular mortality, primary patency of reconstructed vessels in peripheral artery disease patients, and critical lower extremity ischemia, and that it might constitute a potential prognostic marker. In their study of 61 patients with paroxysmal atrial fibrillation (AF), 31 with persistent AF and 71 healthy controls, Zhang et al [16] determined higher MFAP4 levels in patients with AF than in healthy individuals and reported the highest MFAP4 levels in the persistent AF group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serological MFAP4 responses indicate that MFAP4 expression may adapt to specific demands, for example, in chronic liver disease . In addition, increased sMFAP4 has been shown to be a mortality predictor in cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…The protein enhances elastic fiber formation and stimulates smooth muscle cell‐driven vascular and bronchial tissue hyperplasia . Increased circulating MFAP4 (sMFAP4) is a marker of mortality in cardiovascular disease . We hypothesized that MFAP4 can be detected in the synovial membrane from patients with advanced RA and aimed to compare the tissue distribution pattern with findings in patients with late stage OA.…”
mentioning
confidence: 99%